Strengthening capacities for evidence-based policy planning and implementation in Africa: IFPRI’s support to CAADP in 2014-2015 - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As part of IFPRI’s support to CAADP, the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) was established in 2006 to provide policy-relevant analysis, data, and tools necessary to support the formulation and implementation of evidence-based agricultural-sector policies and strategies, as well as to facilitate CAADP policy dialogue, peer review, benchmarking, and mutual learning processes. ReSAKSS is facilitated by IFPRI in partnership with Africa-based CGIAR centers, the African Union Commission (AUC), the NEPAD Planning and Coordinating Agency (NPCA), and leading regional economic communities.